Eficacia de la combinación de dos nucleósidos inhibidores de la transcriptasa inversa con un no-nucleósido, en gatos infectados por el Virus de la Inmunodeficiencia felina - Gómez, N. (2013)
The aim of this study was to report the comparative results using combined antiviral drugs on naturally-infected FIV cats in the asymptomatic and AIDS stages of the disease. The drug combinations evaluated were zidovudine (ZDV) alone and ZDV + lamivudine (3TC) +Nevirapine. Plasma viral load was measured at the beginning of treatment and at one year. Total leucocytes, neutrophils and lymphocyte counts, CD4+/CD8+ ratios and biochemical profile values were also analyzed. Neurological disease was evaluated by evoked potentials determinations. The results showed a better efficacy of the combined therapy vs. ZDV alone, reducing the viral load, increasing the CD4+/CD8+ ratio and improving the clinical signs in the asymptomatic stage. In the AIDS stage the differences between both protocols were not so marked, but the combined therapy produced better results compared with ZDV alone. The auditory and visual evoked potentials put on evidence the neurological disease, even in cats without neurologic signs and were useful to evaluate the evolution of the patients with both protocols contrasted.